A study on the relationship between employee benefits and job satisfaction at Pejabat Daerah Dan Tanah Jerantut / Nurul Syafiqah Muhamad Nor - Muhamad Nor, Nurul Syafiqah (Faculty of Business Management, 2019)
The study was conducted to investigate the relationship between employee benefits and job satisfaction at Pejabat Daerah dan Tanah Jerantut. There are three elements of employee benefits that had been highlighted which are health benefits, salary and rewards that influence employees' job satisfaction. In order, to persue the research and collect data, questionnaires method had been used with the total population of 130 employees with the sample size of 97 employees. To analyze the data collected from the questionnaires, Statistical Package for the Social Science (SPSS) version 23.0 had been used. The results gained from the raw data showed that the two variables were related. From the findings, it showed that salary has high impact on the employees' job satisfaction among the employees at Pejabat Daerah dan Tanah Jerantut. While, health benefits and rewards affected the least toward respondents' job satisfaction. The researcher also included some recommendations for the organization to provide better reward and different variations in rewards in order to increase their job satisfaction, performance and productivity. Other than that, increase staff's awareness about health benefits also strongly recommended as it can influence employees' satisfaction and happiness. At the same time, the researcher also came with the suggestion for the future research.